Deradicalization Narratives from Former Convicts in the Digital Space: Sofyan Tsauri’s YouTube Channel Analysis - Muhyiddin, Muhammad; Priyanto, Sapto (Jurnal Komunikasi Islam, 2023)
This paper examines deradicalization programs from the former terrorism prisoners’ narratives on Sofyan Tsauri’s YouTube channel. Through library research and data collection from digital sources using a phenomenological approach, this paper argues that Sofyan Tsauri becomes an influencer in combating radicalization through his YouTube channel which explains matters related to radicalism, extremism, terrorism, and peace that are likely to have resonance in various locations. Further, Sofyan Tsauri's move has become a vehicle for former terrorists to talk about terrorists from their perspective to overcome various barriers to knowledge hegemony. This article suggests that other terrorists and former convicts are expected to be able to replicate such methods of da'wah in the digital era that are friendly to millennials.